Redukcja zespołów literowych z nadczynnością mięśni skośnych w zabiegach jedno- i obustronnych - Nowakowska, Olimpia; Broniarczyk-Loba, Anna; Loba, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: A-V strabismus patterns may occur with or without oblique muscles overaction and thus require different surgical approach. The aim of our study was to evaluate the efficacy of unilateral vs bilateral surgery for A and V pattern strabismus in children with oblique muscles overaction. Material and methods: A retrospective review of 45 children with oblique muscles overaction was performed. All children underwent unilateral or bilateral oblique weakening procedures over a period of 2 years. The mean reduction of A-V pattern angle was measured in all groups. Results: Among the patients with V pattern, treated with unilateral surgery the mean angle reduction was 11.8∆ ± 6.26∆ and among those who underwent bilateral procedure it was 17.06∆ ± 8.46∆. In A pattern group the mean angle reduction were 8.0∆ ± 2.82∆ and 15.0∆ ± 8.9∆ respectively. Conclusions: The bilateral oblique weakening procedure is significantly more effective (p<0.01) in reducing the angle in A-V patterns than the unilateral surgery. It appears that in A pattern with superior oblique overaction the bilateral surgery gives better results than in V pattern with inferior oblique overaction.